Bidirectional atrioventricular reentrant tachycardia using bilateral accessory pathways. Issue 3 (March 2021) - Yakabe, Daisuke; Fukuyama, Yusuke; Araki, Masahiro; Nakamura, Toshihiro
Abstract: Patients with Wolff-Parkinson-White (WPW) syndrome rarely have multiple accessory pathways (APs). Here, we present a case of a 21-year-old man with the manifest type B WPW syndrome who was experiencing multiple attacks of palpitations. The electrophysiological study revealed two APs located bilaterally: the anterolateral tricuspid annulus and lateral mitral annulus. Atrial/ventricular extrastimulations induced two types of wide QRS tachycardia conducting via two APs in the clockwise and counterclockwise direction. These two APs were eliminated with careful mapping and catheter ablation. <Learning objective: It is extremely rare for patients with the Wolff-Parkinson-White syndrome to have multiple accessory pathways (APs) at the right and left lateral sides along with clinical tachycardia conducting via both pathways. The mechanism of such tachycardia may be due to the differences of effective refractory periods between two APs, long anatomical distance between APs, and no retrograde conduction via the atrioventricular node.>